Attitude and awareness of general population towards radiation hazards and safety: An institutional study - Sneha R Sharma; Freny R Karjodkar; Kaustubh P Sansare; Mohd Saalim; Isha D Mishra; Satyapal Johaley; Shikha N Goyal (Wolters Kluwer Medknow Publications, 2019)
Context: Radiological investigations play a pivotal role in the diagnosis and treatment of a wide range of procedures. Aim: To assess the knowledge regarding adverse consequences of radiological examination and encourage awareness regarding radiation protection amongst general public. Settings and Design: A questionnaire-based cross-sectional study conducted amongst patients visiting the dental outpatient department. Materials and Methods: 1,000 adult male and female patients within the age of 20-70 years who visited the outpatient department during May-July 2017 were included in the study. Statistical Analysis: Comparison of frequencies of responses to each item with age and gender was done using chi square test. For all statistical tests, P < 0.05 was considered to be statistically significant, keeping α error at 5% and β error at 20%. Results: 85.3% participants had visited a hospital earlier and 69.3% had undergone the procedure of an X-ray earlier. Out of those patients, only 24.7% of the participants had any knowledge about the equipment or the procedure while taking a radiograph. 5.2% of the participants were given any safety measures during the radiological procedure. 14.4% had knowledge of the risks and hazards associated with radiation. Conclusions: This short study showed that there is a need for educating the general population about the hazards and risks associated with radiation exposure.